<bdo dir="rtl">أقدم رحلة شنقيطية مدوَّنة: الرحلة المباركة للحاج محمد البشير بن أبي بكر البُرْتُلِي الولاتي إلىٰ الحرمين الشريفين (4021-5021هـ/9871-0971م)</bdo> : Aqdam Riḥla Shinqīṭiyya Mudawwana: al-Riḥla al-Mubāraka lil-Ḥājj Muḥammad b. Abī Bakr al-Burtulī al-Wulātī ilā al-Ḥaramayn al-Sharīfayn (1204-1205H/1789-1790M) - al-Wulātī, Muḥammad b. Abī Bakr al-Burtulī, (Middle East and Islamic Studies E-Books Online, Collection 2021, ISBN: 9789004441286., 2021)
The Oldest Travelogue from Chinguetti [Bilād Shinqīt, present-day Mauritania]: The Blessed Journey of al-Ḥājj Muḥammad b. Abī Bakr al-Burtulī al-Wulātī to the Two Holy Sanctuaries (1204-1205AH/1789-1790CE) was long considered lost. In addition to its historical value and the information it contains on the cultural relations between the western and eastern parts of the Islamic world, it stands out from other Ḥajj travelogues due to the itinerary it follows. The author describes cities, villages, and shrines of righteous people. The work is unique in its account of the unknown Algerian desert of Tenazruft, the landmarks and places along the way, as well as water wells and the notes on whether these are fresh or salty. The travelogue contains many historical references and reports on some ancient Arabic linguistic phenomena and is characterized by its level of detail and cautiousness. إنها أقدم رحلة حج مدونة من بلاد شنقيط (موريتانيا الحالية) والتي ضاعت منذ زمن طويل. بالإضافة إلى قيمتها التاريخية وأهميتها في دراسة التواصل الحضاري بين غرب العالم الإسلامي وشرقه، فهي تتميز عن رحلات الحج الأخرى بمسارها. يصف المؤلف المدن والقرى ومزارات الصالحين. تنفرد الرحلة بوصف الصحراء الجزائرية المجهولة تنزروفت ويصف المعالم والأماكن على طول الطريق إلى الحرمين الشريفين في شبه الجزيرة العربية، وكذلك آبار المياه وما إذا كانت عذبة أو مالحة. والرحلة مليئة بالعديد من الإشارات التاريخية بالإضافة إلى بعض الظواهر اللغوية العربية القديمة وتتميز بدقة الوصف والاحتياط في الرواية.